Physics Student Misconception: Relative Velocity, Time Dilatation, and Length Contraction - Serly Anggraini Listianingrum; Jumadi Jumadi; Rizki Zakwandi (Jurnal Ilmiah Pendidikan Fisika, 2022)
This study aims to analyze senior high school students' misconceptions on the relativity topics of relative velocity, time dilation, and length contraction. The qualitative descriptive method was used in this study to explain student misconceptions from the student, documents, and observations during problem-solving. Six students take an extra course in an independent learning center to participate in this study. The student was classified as two high, middle, and low levels. The data was collected from student reports, interviews, and observations. The results show a considerable misconception of students' understanding of relativity topics. This study identifies that student misconceptions come from the learning process, resources, and teacher confirmation. Thus, there is a need for attention and remediation regarding the relativity material because it will affect the concept of students to the next level.